PERBANDINGAN CERITA NOVEL DENGAN FILM DI BAWAH LINDUNGAN KABAH - Ibrasma, Rimata; Hasanuddin WS, Hasanuddin WS; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2013)
The purpose of this article is (a) to describe the story of episode novel Di Bawah Lindungan Kabah written by Hamka, (b) to describe the story of episode Di Bawah Lindungan Kabah movie director by Hanny R. Saputra, (c) to describe the similarity and differences the story of episode novel with Di Bawah Lindungan Kabah movie. The Data of this study is the story of episode novel Di Bawah Lindungan Kabah written by Hamka and Di Bawah Lindungan Kabah movie director by Hanny R. Saputra. Analysis technique is with ekranisasi theory. The finding of the study showed that the decreasing episode of the story novel Di Bawah Lindungan Kabah written by Hamka in Di Bawah Lindungan Kabah movie director by Hanny R. Saputra become 61 stories of episode. Additional of the story in Di Bawah Lindungan Kabah movie director by Hanny R. Saputra become 89 stories of episode. The change of variation event, character and background the story of episode in novel Di Bawah Lindungan Kabah written by Hamka and Di Bawah Lindungan Kabah movie director by Hanny R. Saputra become 14 stories of episode. Â Keywords: novel, film, comparation of novel with film, ekranisasi